Chilean Geopolitics and Its Military Development (1905-2018) [la Geopolítica Chilena y Su Desarrollo Militar (1905-2018)] - Garay-Vera, C (Escuela Militar de Cadetes, 2021)
This article postulates the importance of military geopolitics as the central pillar of Chilean geopolitical thought. For the author, this is the product of both the emphasis on advising and executing guidelines in this field and the theoretical reflection within the Chilean Army and Navy since the beginning of the 20th Century. From this perspective, the development of geopolitics has been linked to notions of strategy, political geography, and military planning. The article suggests four phases of development that depend on the country s political context and the state s greater or lesser access to decision-making. As a result, it is established that the national political context, the military autonomy, or the civil control of the Armed Forced, among other factors, have influenced the development of geopolitics in Chile. © 2021 Revista Cientifica General Jose Maria Cordova.